Nasionalisme dalam Teror di Mandar Tahun 1947 - Abd Rahman Hamid (Universitas Islam Negeri Alauddin Makassar, 2015)
The wishes became a new state (republic) was paid expensively by the citizen of Mandar. On February 1947, Westerling Army did a massacre at Galung Lombok and also the surrounding area. The victims were accused as an extremist, robber, and slayer. They were executed without mercy and of course disobey the legal procedure. That event became a history crossbar in this area to maintain Republic of Indonesia from Netherland Army. The movement has widely influence, not only in South Celebes but also in Java and Borneo. Moreover, civilian’s struggle which organized through KRIS MUDA and GAPRI 5.3.1. Through the results of this study has been found the relation between nationalism and religion. Moreover, there were another organizations, especially ALRI-PS had some role to assist the Republic. As an implication, Mandar was pointed as the location of terror target by Westerling. It seemed on how important the influence of this area’s movement to fight for freedom